Analisis Implikatur Percakapan pada Komik Digital “Pupus Putus Sekolah” Karya Kurnia Harta Winata - Dara Aprilia Maharani; Fadhlina Hanifa Lubis; Delviani Yani Manik; Sakinah Rangkuti; Nirmawan (Universitas Serambi Mekkah, 2025)
This study aims to analyze the forms of conversational implicature found in the digital comic Pupus Putus Sekolah by Kurnia Harta Winata. The comic was selected because it contains numerous dialogues that reflect everyday teenage interactions, making it relevant for analysis from a pragmatic perspective, particularly using Grice’s theory of conversational implicature. The research employs a descriptive qualitative method with content analysis techniques. The data consists of dialogue excerpts between characters in the comic that contain implicit meanings. The analysis reveals that the conversational implicatures in the comic fall into two main categories: conventional implicatures and non-conventional (conversational) implicatures. The most dominant type of non-conventional implicature observed involves violations of the cooperative principle, particularly the maxims of quality and relevance. These findings suggest that digital comics can serve as effective media for conveying social messages through indirect communication strategies. Furthermore, this research contributes to the field of pragmatics, particularly in the context of visual literary works and digital communication.